Students’ Grammatical Errors in Writing Descriptive Texts - Elfa Novelia; Faisal Faisal (JoLLA: Journal of Language, Literature, and Arts, 2023)
The primary objective of this study was to investigate and describe the various types of grammatical errors observed in written descriptive texts of seventh-grade students. A quantitative research design was employed, aligned with the recommended research project design proposed by Creswell and Plano Clark (2011). The data collection process involved analyzing students' written descriptive texts. A total of 82 errors were identified and categorized according to their frequency, namely omission, misformation, addition, and misordering. The study argued that the nature of the formative assessment and the national examination, with an emphasis on grammatical dimensions, were significant factors influencing these errors. These findings provide valuable insights into comprehending specific grammatical error patterns, thus facilitating the development of targeted instructional strategies to address these issues effectively. Keywords: descriptive texts; formative assessment; grammatical errors Kesalahan Tata Bahasa Siswa dalam Menulis Teks Deskriptif Penelitian ini bertujuan untuk menyelidiki dan menggambarkan jenis-jenis kesalahan gramatikal yang ditemukan dalam teks deskriptif tulisan siswa kelas tujuh. Penelitian ini menggunakan desain penelitian kuantitatif sesuai dengan desain proyek penelitian yang direkomendasikan oleh Creswell dan Plano Clark (2011). Data dikumpulkan menggunakan dokumen - teks deskriptif tulisan siswa. Ditemukan 82 kesalahan yang diklasifikasikan berdasarkan urutan kesalahan paling sering hingga paling jarang terjadi, yaitu penghilangan, pembentukan salah, penambahan, dan pengurutan yang salah. Penelitian ini berargumen bahwa faktor yang diyakini mempengaruhi kesalahan tersebut adalah sifat penilaian formatif dan ujian nasional, dengan penekanan pada dimensi gramatikal. Temuan ini memberikan wawasan berharga dalam memahami pola kesalahan gramatikal tertentu, sehingga memudahkan pengembangan strategi pembelajaran yang tepat untuk mengatasi masalah tersebut dengan efektif. Kata kunci, teks deskriptif, asesmen formatif, kesalahan tata bahasa,